Experiencias De Duelo En Las Familias Que Enfrentaron El Suicidio De Un Miembro Menor De Edad En El Municipio De Manaure - La Guajira (2023)
Living the experiences of grief and coping with the death of a loved one is and will continue to be one of the most complex events that people must go through, however, having to experience grief or the loss of a family member in an unexpected way such as by suicide makes it even more complicated for family members, taking into account that the experiences of grief are lived very differently by each of the individuals. This is how the present research project aims to understand the experiences of grief in families who faced the suicide of one of their minor members in the municipality of Manaure La Guajira, having as a study population 5 families who have lived this experience, it also has a qualitative study methodology since it is based on the historicalhermeneutical epistemological bases in its attempt to describe and study significant human phenomena in a detailed and precise way, based on previous theoretical assumptions and change in practical understanding, It is also based on interpretative phenomenological analysis, in its search for how people give meaning to their experiences, leaving as main findings changes in the lifestyles of the affected families, since the experience of grief changed the way in which they perceive the reality and how they see their life now, it is also evidenced that they deny on in the grieving process, preventing families from saying goodbye and facing reality.